Are Affective Temperaments, Emotional Abuse, and Neglect Involved in Mentalization Abilities in Patients With Psychiatric Disorders?. Issue 4 (30th April 2022) - Berardelli, Isabella; Sarubbi, Salvatore; Sarli, Giuseppe; Rogante, Elena; Del Casale, Antonio; Erbuto, Denise; Innamorati, Marco; Lester, David; Pompili, Maurizio
Abstract: Patients who have experienced emotional abuse and neglect often develop psychiatric disorders in adulthood. However, whether emotional abuse, neglect, and mentalization abilities relate to one another and the role of possible mediators of this relationship in psychiatric patients are still unknown. We evaluated the potential role of affective temperament as a mediator of the relationship between emotional abuse and neglect and mentalization. We performed a cross-sectional study of 252 adult psychiatric inpatients. The Childhood Trauma Questionnaire, Mentalization Questionnaire, and Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A) were administered. Results showed a significant indirect effect of emotional abuse and neglect on scores on the Mentalization Questionnaire through the TEMPS-A ( b = 0.25, 95% confidence interval [0.143–0.375]), demonstrating that affective temperament mediates the relationship among emotional abuse, neglect, and mentalization impairment in psychiatric patients. A careful evaluation of mentalization abilities in patients with psychiatric disorders and who have a history of emotional abuse and neglect is necessary for a better understanding of psychopathology and for the choice of therapeutic strategies.